PENDAMPINGAN PEMANFAATAN MULTIMEDIA PEMBELAJARAN MENGGUNAKAN OBS PADA MADRASAH ALIYAH SUNNIYYAH SELO GROBOGAN - Moh. Muthohir; Dendy Kurniawan (CV. Denasya Smart Publisher, 2026)
This community service activity aims to improve the competency of teachers at the Sunniyyah Selo Grobogan Islamic Senior High School in utilizing video-based multimedia learning using the Open Broadcaster Software (OBS) application as a means of supporting a more interactive teaching and learning process. The main problems faced by partners were the low utilization of digital learning media, teachers' limited knowledge regarding screen recording and audiovisual material management, and the lack of simple standards for creating independent learning content in the madrasah. The implementation method included needs analysis, socialization of the importance of learning multimedia, technical training on the use of OBS, mentoring in learning video production practices, and evaluation of results through product assessments and participant satisfaction questionnaires. The results of the activity showed an increase in teachers' understanding of the concept of learning multimedia, their ability to install and configure OBS, create simple scenarios (storyboards), and produce at least one learning video for the subjects they teach. This activity also encouraged the madrasah's commitment to developing a learning video content bank as a learning resource that can be used sustainably in both face-to-face and online learning.